2022
DOI: 10.2478/jvetres-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Two centrifugal flotation techniques for counting gastrointestinal parasite eggs and oocysts in alpaca faeces

Abstract: Introduction The alpaca (Vicugna pacos) is a camelid native to South America, but the species has wide distribution outside its natural habitat and is found in various countries on other continents, Poland being one in Europe. Parasitic infections affect the productivity and health of alpacas. The aim of the study was to estimate the parasite loads in alpacas kept in Poland with the use of two direct centrifugal flotation methods. Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, Haemonchus sp. Cobb (order Strongylidae; family Trichostrongylidae) infection also was noted in members of the Artiodactyla order and Cervidae family inhabiting Polish forests, including roe deer Capreolus capreolus Linnaeus, fallow deer Dama dama Linnaeus, red deer Cervus elaphus Linnaeus, and moose Alces alces Linnaeus (Filip & Demiaszkiewicz, 2016; Pyziel‐Serafin et al, 2023). A previous study revealed high within‐population variations among different populations of H. contortus (Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Haemonchus sp. Cobb (order Strongylidae; family Trichostrongylidae) infection also was noted in members of the Artiodactyla order and Cervidae family inhabiting Polish forests, including roe deer Capreolus capreolus Linnaeus, fallow deer Dama dama Linnaeus, red deer Cervus elaphus Linnaeus, and moose Alces alces Linnaeus (Filip & Demiaszkiewicz, 2016; Pyziel‐Serafin et al, 2023). A previous study revealed high within‐population variations among different populations of H. contortus (Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%